2021
DOI: 10.1177/20587392211002986
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pathways and potential therapies for COVID-19: A mini review

Abstract: The public health crisis of the novel coronavirus disease (COVID-19) is alarming since January 2020. COVID-19 genome (SARS-CoV-2) is related to other highly pathogenic coronaviruses SARS-CoV (severe acute respiratory syndrome coronavirus) and MERS-CoV (Middle East respiratory syndrome coronavirus). Amino acid substitutions in some of SARS-CoV-2 proteins resulted in mutations proposing more virulent and contagious properties for this novel virus. Coronavirus penetrates the host cell via endocytosis and once inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 242 publications
0
5
0
Order By: Relevance
“…Previous studies have suggested that IL-1β and IL-6 are key pro-inflammatory biomarkers in initiation of the acute phase response, resulting in a broad range of local and systemic events such as fever and recruitment of leukocytes. 18 , 19 Increased IL-17 in patients with COVID-19 pneumonia has been observed in other studies, 40 and Th-17 cells contribute in the cytokine storm triggered by SARS-CoV-2. 41 Further, elevations of IL-2, IL-4 and IL-17 levels are observed in COVID-19 patients’ serums with prominent lung damage.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies have suggested that IL-1β and IL-6 are key pro-inflammatory biomarkers in initiation of the acute phase response, resulting in a broad range of local and systemic events such as fever and recruitment of leukocytes. 18 , 19 Increased IL-17 in patients with COVID-19 pneumonia has been observed in other studies, 40 and Th-17 cells contribute in the cytokine storm triggered by SARS-CoV-2. 41 Further, elevations of IL-2, IL-4 and IL-17 levels are observed in COVID-19 patients’ serums with prominent lung damage.…”
Section: Discussionmentioning
confidence: 53%
“… 17 As declared, the intense and uncontrolled inflammation induced by SARS-CoV-2 leads to severe disease, increased morbidity, and mortality, so dampening and downregulating the inflammatory response and reducing its intensity could be a promising therapy. 18 , 19 Exploring broad with patients in different geographical areas and ethnical groups might pave the way toward controlling SARS-CoV-2 immunopathogenesis. 20 The challenges would be to increase knowledge and understand the physiopathology of COVID-19 and emerging mutants.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory activity of both species has been identified in rat and mouse inflammation models [ 28 , 29 ]. Recent therapeutic approaches for COVID-19 patients recommend the use of anti-inflammatories in combination with antivirals [ 30 ]. Since Stachytarpheta cayennensis extract has anti-inflammatory activity in addition to antiviral activity, it could also be used in the inflammatory stages of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The immune response is responsible for inflammation and lung injury when the virus fights. Apoptosis of infected cells releases new viral particles [ 34 , 35 ]. Repetitive injury, together with viral replication, leads to the loss of type 1 and 2 pneumocytes, which generates diffuse alveolar damage that ultimately culminates in acute respiratory distress syndrome (ARDS) [ 34 , 35 ].…”
Section: Route Of Entry and Endotheliiitismentioning
confidence: 99%